Psychological Well-Being of Adolescents Experiencing Parent-lessness: Challenges, Resilience, and Adaptation - Stephanie Magdalena M.; Arthur Huwae (Bulletin of Counseling and Psychotherapy, 2026)
Adolescents who experience parent-lessness face numerous challenges that may negatively affect their mental health. This study aims to describe the psychological well-being profile of adolescents who experience parent-lessness. The research employed a qualitative method with a descriptive phenomenological design. A total of five participants, two male and three female adolescents who experienced parent-lessness, were selected using purposive sampling techniques. Data were collected through face-to-face semi-structured interviews the lasted between 31 and 53 minutes. The participants were male and female adolescents aged 18-21 years who experienced parental neglect. They came from divorced families, foster families, lived separately from their parents, or lacked parental presence both physically and emotionally. The themes that emerged from the six dimensions of psychological growth included new experiences that shape the self, openness, self-understanding, and awareness of personal potential. Strong feelings of inferiority and uncertainty about the future were also reported by the participants. The findings indicate that adolescents who experience parent-lessness tend to have lower levels of psychological well-being. This condition contributes to a lack of trust in others, particularly toward individuals who have caused them emotional pain. Nevertheless, some participants continued to believe that their parents simply did not know how to express affection. The implications of this study suggest that there are limitations that provide opportunities for further development and a more in-depth exploration of the psychological well-being of parentless adolescents.